“Peer teaching program using ecrif and pdp frameworks to improve speaking and listening skills in the first level of the pedagogic English major at the technical University of Cotopaxi” . - Dávalos Goméz, Helen Mabel (2023)
Speaking and listening are fundamental skills that English students must master to become competent users of the language. In the context of teaching English as a Foreign Language (EFL), many students face several problems when developing the above-mentioned skills. That’s why the present project was carried out to describe pre-service teachers’ and students’ experiences in the implementation of the peer teaching program using ECRIF (Encounter, Clarify, Remember , Internalize and Fluently) and PDP (Pre-stage, During-stage and Post-stage) frameworks at the Technical University of Cotopaxi. This implementation idea came from a Project called “Implementing peer-teaching program based on two learner-centered frameworks to enhance the performance in speaking and listening skills of weak students from first, second and third term of English Major at Technical University of Cotopaxi”. The researcher applied a qualitative approach, as well as a survey with open-ended, and closed-ended questions that were used as data collection for students. The reflection guide was used also as an instrument to collect data for pre-service teachers. Five first term students of English Major at Technical University of Cotopaxi were the population. The main findings showed positive, and negative aspects about the implementation. The positive results were that by implementing this program with the use of ECRIF and PDP framework 80% percent of students were able to improve their speaking and listening skills through different techniques applied (guessing games, role plays, collaborative work and matching activities). Regarding the material, a major percent of students felt very satisfied with the material implemented whereas a few percent of students felt satisfied, and the rest felt comfortable. In that case, a high percentage of the students felt that this program contributed to their learning improvement. Conversely, the pre-service teachers faced some drawbacks such as lack of class participation, technological problems, lack of time management for the activities, unknown vocabulary for the students and as a student’s suggestion the materials for the class development could be improved by using more technological tools. However, as negative points, the pre-service teachers were unable to give clear instructions, and the didactic material had an unfamiliar vocabulary for the students which did not allow them to develop the activities in the requested time. Based on these findings, the researchers suggest strengthening the present project by including it in the curricula to provide a better learning experience for students.